Densities in large permutations and parameter testing. (February 2017) - Glebov, Roman; Hoppen, Carlos; Klimošová, Tereza; Kohayakawa, Yoshiharu; Král', Daniel; Liu, Hong
Abstract: A classical theorem of Erdős, Lovász and Spencer asserts that the densities of connected subgraphs in large graphs are independent. We prove an analogue of this theorem for permutations and we then apply the methods used in the proof to give an example of a finitely approximable permutation parameter that is not finitely forcible. The latter answers a question posed by two of the authors and Moreira and Sampaio.